THE OXFORD ENGLISH DICTIONARY IN MODERN LINGUISTICS AND EDUCATION - Yoqubova Mohichehra; Xalilova Mohichehra; Abdullayeva Ruxsora (TADQIQOTLAR, 2026)
Annotation This article examines the importance of the Oxford English Dictionary (OED) in modern linguistics and education. The OED is widely recognized as one of the most authoritative and comprehensive dictionaries in the world. It provides not only definitions of words but also detailed historical records, including their origins, pronunciation, and changes in meaning over time. This study explores how the OED contributes to vocabulary development, critical thinking, and effective communication skills. In addition, it highlights the role of the dictionary in connecting language learning with historical, cultural, and social contexts. The research shows that the OED is not just a linguistic tool but also a valuable educational resource.